Decreased Adiponectin Levels and Effect of Atorvastatin Treatment in Hyperlipidemic Patients - Özkan, Yusuf; Akbulut, Handan; Koca, Süleyman Serdar; Gençer, Vedat; Dönder, Emir (Fırat University, 2007)
Objectives: Atherosclerotic diseases such as coronary heart disease, myocardial infarction and stroke are leading causes of morbidity and mortality. Hyperlipidemia is among the major risk factors for atherosclerotic diseases. Atorvastatin, a member of statins wich is a potent lipid lowering drugs is used widely in hyperlipidemia. Serum levels of adiponectin that is produced in adipose tissue and that regressed atherosclerosis were shown to fall down in the presence of such atherosclerosis risk factors as hypertension, diabetes and hyperlipidemia. In the present study we aimed to examine serum adiponectin levels in hyperlipidemia and at the end of atorvastatin treatment. Material and Methods: The study enrolled 26 non-diabetic hyperlipidemic patients and 10 healthy individuals matching hyperlipidemia group in terms of age, sex, body mass index and blood pressure. The 26 hyperlipidemic patients were treated with 20 mg/day atorvastatin for 8 weeks. Serum lipid and adiponectin levels were examined at the beginning of the treatment and after 8 weeks. Results: Adiponectin levels were found 18.8±6.8 µg/mL in healthy individuals and 3.7±1.3 µg/mL in hyperlipidemic patients, the difference between them being statistically significant (p

Giriş: Koroner arter hastalığı, miyokard infarktüsü, inme gibi ateroskleroz temelli hastalıklar morbidite ve mortalitenin önde gelen sebeplerindendir. Hiperlipidemi aterosklerotik hastalıkların majör risk faktörlerindendir ve hızlanmış ateroskleroz ile sonuçlanmaktadır. Potent lipid düşürücülerden statinlerin bir üyesi olan atorvastatin hiperlipidemide yaygın olarak kullanılmaktadır. Yağ dokudan üretilen, aterosklerozu gerileten adiponektinin; obezite, hipertansiyon, diyabet, hiperlipidemi gibi ateroskleroz risk faktörlerinin varlığında serum düzeylerinin azaldığı ortaya konulmuştur. Bu çalışmada hiperlipidemide ve atorvastatin tedavisi sonunda serum adiponektin düzeylerini incelemeyi amaçladık. Gereç ve Yöntem: Çalışmaya non-diyabetik hiperlipidemik 26 olgu ile yaş, cinsiyet, vücut kitle indeksi ve kan basınçları hiperlipidemi grubuna uygun 10 sağlıklı olgu alındı. Hiperlipidemik 26 olgu 20 mg/gün atorvastatin ile 8 hafta süre tedavi edildi. Tedavinin başlangıcında ve 8 hafta sonra serum lipit ve adiponektin düzeylerine bakıldı. Bulgular: Sağlıklı olgularda adiponektin düzeyi 18.8±6.8 µg/mL iken hiperlipidemi grubunda 3.7±1.3 µg/mL tespit edildi ve aralarındaki fark istatistiksel olarak anlamlı idi (p
Hiperlipidemik Olgularda Azalmış Serum Adiponektin Düzeyi ve Atorvastatin Tedavisinin Etkisi